Music Communication in Juicy Luicy’s Lyrics: Emotional Voices of Generation Z - Hera Nur Aini; Zainal Abidin; Celvin Dwi Putra Mudianto (JOSAR (Journal of Students Academic Research), 2025)
This study aims to analyze the emotional representation in the lyrics of Juicy Luicy’s popular songs among Generation Z. Employing Roland Barthes’ semiotic framework and Stuart Hall’s theory of representation, this research explores how emotional meanings are constructed through linguistic and symbolic signs in the lyrics and how Generation Z audiences interpret them based on their social context. The study focuses on four songs: “Lantas”, “Tanpa Tergesa”, “Lampu Kuning”, and “Sialan", selected for their digital popularity and emotional resonance on platforms Spotify and YouTube. The findings reveal that the lyrics represent emotions such as dilemma, regret, uncertainty, and loss through simple diction, visual metaphors, and accessible symbols. These songs deliver emotional depth not only on a literal level but also connotatively, forming cultural myths around love and longing. Generation Z decodes these lyrics through the lens of their personal experiences, treating them as a reflective space for articulating emotional identity. Moreover, the lyrics serve as a medium for managing emotional stress and building social connections through shared empathy. Thus, the study affirms that Juicy Luicy’s lyrics function as a form of emotional communication and cultural representation in the lives of Generation Z.